Musical meaning and expression - Davies, Stephen (New York Cornell University Press, 1994)
We talk not only of enjoying music, but of understanding it. Music is often taken to have expressive import--and in that sense to have meaning. But what does music mean, and how does it mean? Stephen Davies addresses these questions in this sophisticated and knowledgeable overview of current theories in the philosophy of music. Reviewing and criticizing the aesthetic positions of recent years, he offers a spirited explanation of his own position.